2014
DOI: 10.1017/s1074070800000651
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Technical, Allocative, Economic, and Scale Efficiency of Rice Production in Arkansas Using Data Envelopment Analysis

Abstract: Data envelopment analysis is used to calculate technical, allocative, economic, and scale efficiencies for fields enrolled in the University of Arkansas Rice Research Verification Program. The results reveal most fields have high technical and scale efficiencies, implying inputs are used in minimum levels necessary to achieve given output levels and fields are close to optimal in size. However, most fields exhibit allocative and economic inefficiencies and do not use inputs in the right combinations necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
2
20
0
9
Order By: Relevance
“…A number of studies have been carried out to analyse the efficiency of agriculture using the DEA. Examples of such studies include Chavas and Aliber (1993), Sharma et al (1999), Dhungana et al (2004), Murthy et al (2009), andWatkins et al (2014). There is a particular dearth of studies that should analyze the economic efficiency of smallholder vegetable farms.This study is an attempt to evaluate the efficiency of farms so as to be able to generalize the findings at the national level.…”
Section: Theoretical and Empirical Analysismentioning
confidence: 99%
“…A number of studies have been carried out to analyse the efficiency of agriculture using the DEA. Examples of such studies include Chavas and Aliber (1993), Sharma et al (1999), Dhungana et al (2004), Murthy et al (2009), andWatkins et al (2014). There is a particular dearth of studies that should analyze the economic efficiency of smallholder vegetable farms.This study is an attempt to evaluate the efficiency of farms so as to be able to generalize the findings at the national level.…”
Section: Theoretical and Empirical Analysismentioning
confidence: 99%
“…Some studies have applied both approaches to the same sets of data [such as Reinhard et al (2000); Wadud and White (2000); Iráizoz et al (2003); Latruffe et al (2004); Alene et al (2006); Ghorbani et al (2010); Theodoridis and Anwar (2011)] and found that the estimation result of both approaches is not much different. This evidence shows that the choice of which approach to be used is somewhat arbitrary (Dhungana et al, 2004;Watkins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This study used the DEA approach because it does not impose parametric restrictions on the underlying technology (Chavas & Aliber, 1993;Featherstone et al, 1997;Fletschner & Zepeda, 2002;Wu & Prato, 2006;Watkins et al, 2014). Framework of the discussion in this paper is followed sequentially by methodology, results and discussion, and conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the method of cultivation, the efficient of production input usage also very determines the production of rice farming (Hormozi et al, 2013;Ojogho and Alufohai, 2010;Wen et al, 2011;Maruyama et al, 2014;Watkins et al, 2014). The effort of rice production increasing through the efficiency of input usage became the right choice.…”
Section: Introductionmentioning
confidence: 99%